PENGARUH IKLIM PANAS TERHADAP DEHIDRASI DAN KELELAHAN PADA CLUB SEPEDA ONTHEL (Roadster Bicycle) di TANGGUNGHARJO - Swastika Ramadhanty Eka Putri; Upik Nurbaiti; Fianti Fianti (Universitas Lambung Mangkurat, 2021)
The sector transportation is one of the main causes of environmental damage. Environmental changes that occur will affect climatic conditions in general. This study aims to determine the effect of hot climate on routine cycling activities on the dehydration status and fatigue of a person cycling based on changes in body weight, knowledge of dehydration and fatigue, temperature and the level of heat index. This research was conducted by measuring the body weight, humidity, and temperature of the cyclists before and after training. Measurements were made on November 6, 2020 with a total of 20 subjects who are members of the Tanggungharjo bicycle club. From the results of simple analysis, it is obtained that the average number is 153 for those aged 30 years and under with the ideal limit category, while at the age of 30 years and above the average figure is 156.1 with the tolerance limit category. Therefore, the level of dehydration and fatigue can include several factors such as age, temperature, humidity and body weight.